The Analysis of Sociopath of Louis Bloom’s Character in Nightcrawler - Yuli Angraini (English Department, University of Riau Kepulauan, Batam,Indonesia, 2016)
The writer chose one of literary works—film entitled “The Analysis of Sociopath of Louis Bloom’s Character in Nightcrawler” to be anlyzed. The writer interested to analyze the main character in this film—Louis who used all people around him for the sake of his own intention. He even did not care if people whom he used finally dead. He even recorded the murded scene as calm as it was nothing just casual events that could happen anytime. The purpose of this study was to analyze the types of sociopath character in Louis Bloom and to describe how it can affect his perspective towards his goal. The method of this study was a descriptive. The writer watched Nightcrawler movie to observe the main chharacter and he manipulated people to smooth his way. The writer also read the movie script to understand Louis’ character deeper.To analyze the sociopath of main character, the writer used the psychological approach of Grossman’s theory of psychoanalysis Keywords: sociopath character and psychological approach